Food and nutrition security in Eurasia: Evolution, shocks and policies - Burkitbayeva, Saule; Swinnen, Johan; Warrinnier, Nele (Voprosy Ekonomiki N. P., 2020)
Food and nutrition security is at the forefront of policy making around the globe. This study focuses on a number of Eurasian countries, namely the Russian Federation, Kazakhstan, Uzbekistan, Armenia, Tajikistan and Kyrgyzstan. From under-nutrition to various forms of malnutrition and obesity, these countries face different challenges when it comes to food and nutrition security. Over the last three decades, their situations have been affected by a number of important income shocks, including through falling remittances from relatively wealthier to poorer countries. This paper analyzes these developments and discusses how these countries have introduced policies to address food and nutrition security.